2022
DOI: 10.3389/fpsyt.2022.797952
|View full text |Cite
|
Sign up to set email alerts
|

The Transdiagnostic Relevance of Self-Other Distinction to Psychiatry Spans Emotional, Cognitive and Motor Domains

Abstract: Self-other distinction refers to the ability to distinguish between our own and other people's physical and mental states (actions, perceptions, emotions etc.). Both the right temporo-parietal junction and brain areas associated with the human mirror neuron system are likely to critically influence self-other distinction, given their respective contributions to theory of mind and embodied empathy. The degree of appropriate self-other distinction will vary according to the exact social situation, and how helpfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 317 publications
1
9
0
Order By: Relevance
“…In the second process, our results demonstrate that fantasy is related to emotional regulation, and this relationship is moderated by personal distress. Within the social cognitive domain, indicators of low self-other distinction are motor imitation and emotion contagion when we effectively take on the physical and emotional states of others ( Eddy, 2022 ). Frequent emotion contagion may lead to emotional dysregulation; detachment from emotional experiences may help combat personal distress ( Eddy, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second process, our results demonstrate that fantasy is related to emotional regulation, and this relationship is moderated by personal distress. Within the social cognitive domain, indicators of low self-other distinction are motor imitation and emotion contagion when we effectively take on the physical and emotional states of others ( Eddy, 2022 ). Frequent emotion contagion may lead to emotional dysregulation; detachment from emotional experiences may help combat personal distress ( Eddy, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Within the social cognitive domain, indicators of low self-other distinction are motor imitation and emotion contagion when we effectively take on the physical and emotional states of others ( Eddy, 2022 ). Frequent emotion contagion may lead to emotional dysregulation; detachment from emotional experiences may help combat personal distress ( Eddy, 2022 ). For example, during the last decade, there has been a growing body of research on the abnormality of fantasy and personal distress in empathy (e.g., Harari et al, 2010 ; New et al, 2012 ; De Meulemeester et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Self-other distinction describes an intraindividual concept or experience, but it is likely to be closely linked to empathy and social behavior. Therefore while self-other distinction may be applied to different domains (e.g., motor, cognitive, and emotional: see Eddy, 2022 ), measuring self-other distinction may appear to overlap with affective empathy, when applied to emotional experience. For example, when self-other distinction within an individual is less pronounced, it may facilitate greater affective empathy or manifest as greater resonance with the emotion of another, such as experiencing personal distress in response to another person’s distress (e.g., Eddy, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore while self-other distinction may be applied to different domains (e.g., motor, cognitive, and emotional: see Eddy, 2022 ), measuring self-other distinction may appear to overlap with affective empathy, when applied to emotional experience. For example, when self-other distinction within an individual is less pronounced, it may facilitate greater affective empathy or manifest as greater resonance with the emotion of another, such as experiencing personal distress in response to another person’s distress (e.g., Eddy, 2022 ). Intact CE in the context of lower AE, and many characteristics associated with narcissism, such as socially competitive emotions, seem to imply higher self-other distinction in highly narcissistic individuals ( Eddy, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers concluded that both the right temporo-parietal junction and brain areas associated with the human mirror neuron system are likely to critically influence self-other distinction. The appropriate degree of self-other distinction will vary according to the exact social situation, e.g., affective empathy may involve low self-other distinction, whereas understanding false belief requires higher self-other distinction ( Eddy, 2022 ). These studies demonstrate that there is a difference between the processing of the ‘self’ perspective and the processing of the ‘other’ perspective.…”
Section: Introductionmentioning
confidence: 99%